COGNITIVE AND EDUCATIONAL IMPORTANCE OF THE PRINCIPLES IN GUIDING BY AMIR TEMUR - Rzaeva, J.K. (FAN va JAMIYAT, 2019)
The article is devoted to the description of the principles of governing by which the famous state leader Amir Timur was quided in his life. They were given in his book “Timuri-Tuzuki” that was translated into many languages. These principles remain valuable today, and they play a great role in the education of young generation.